2011
DOI: 10.1016/j.juro.2010.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Oral Desmopressin for Nocturnal Polyuria in Patients With Benign Prostatic Hyperplasia: A Double-Blind, Placebo Controlled, Randomized Study

Abstract: Low dose oral desmopressin is an effective and well tolerated treatment for nocturnal polyuria in the lower urinary tract symptoms of patients with benign prostatic hyperplasia. Long-term desmopressin therapy gradually decreases serum sodium and it might induce hyponatremia even in patients without initial hyponatremia. For long-term desmopressin administration serum sodium should be assessed carefully, at least at 1 week after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 25 publications
1
62
0
1
Order By: Relevance
“…nowadays, desmopressin is the most common prescribed medication for nocturia related to nocturnal polyuria. In a randomized double-blind placebo-controlled study, Wang et al [7] evaluated the efficacy of low-dose oral desmopressin in patients with BPH and nocturia associated with nP and found that desmopressin resulted in a significant decrease in nocturnal voiding frequency and the volume of nocturnal urine. However, this study was evaluating desmopressin only effect on nocturia in aging patients with BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nowadays, desmopressin is the most common prescribed medication for nocturia related to nocturnal polyuria. In a randomized double-blind placebo-controlled study, Wang et al [7] evaluated the efficacy of low-dose oral desmopressin in patients with BPH and nocturia associated with nP and found that desmopressin resulted in a significant decrease in nocturnal voiding frequency and the volume of nocturnal urine. However, this study was evaluating desmopressin only effect on nocturia in aging patients with BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Many double-blind placebo-controlled studies were conducted to assess the effect of BPH medical therapies on nocturia associated with BPH and also to assess the effect of desmopressin therapy in BPH patients with nocturnal polyuria (nP) [5,7]. However, treatment for nocturia has been reported to be less satisfactory than treatment of other lUtS and remains one of the most difficult lUts to treat.…”
Section: Introductionmentioning
confidence: 99%
“…6 Oral desmopressin had effects in patients with BPH especially for nocturnal polyuria. 7 So desmopressin was included for medical treatment modality in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Wang ve arkadaşları AÜSS ve noktürinin bulunduğu 115 hastalık çalışmalarında, plasebo ile desmopressin tedavisini karşılaştırmışlar ve iki grup arasında anlamlı fark tespit etmişlerdir. [10] Çalışmamızda her iki grupta noktüri açısından bazal değerler ile üçüncü ay kontrol değerleri arasında istatistiksel anlamlı fark tespit edildi.…”
Section: Bulgularunclassified